Effect of microstructure on corrosion of welded joints of X80 steel in water saturated supercritical CO2. Issue 4 (1st July 2019) - Deng, Hongda; Cao, Xianlong; Yan, Yongbo; Xie, Kuanya
Abstract : Purpose: The purpose of this paper is to research whether microstructure varieties of zones at welded joints pose a tremendous effect on its corrosion in SC-CO2 . Design/methodology/approach: The interrelation between the corrosion and microstructure of base metal (BM), fine grain heat affected zone (FHAZ), coarse grain heat affected zone and weld metal (WM) in welded of X80 steel in water saturated supercritical CO2 was studied by using optical microscope, weight loss test, electrochemical measurements and surface analytical techniques. Findings: The all subzones of X80 weld joints were attacked by SC-CO2 corrosion and showed flower-like corrosion scale spots consisted of granular FeCO3 . The most severe corrosion appeared at WM due to lower proportion of ferrite to pearlite, but the slightest corrosion displayed at BM. GHAZ with larger grains and more polygonal ferrite exhibited more severe corrosion than that at BM. Due to its smaller grain, FHAZ displayed comparatively more severe corrosion to that at BM. Originality/value: There exists close interrelation between the corrosion and microstructure of the welded carbon steel in water saturated supercritical CO2 .